Effect of Tempering Temperature on Impact Wear Behavior of 30Cr3Mo2WNi Hot-Working Die Steel - Zhang, Cheng; Li, Pu; Wei, Shizhong; You, Long; Wang, Xiaodong; Mao, Feng; Jin, Dongliang; Chen, Chong; Pan, Kunming; Luo, Cheng; Li, Jingkui (Frontiers in Materials, 2019)
Effect of tempering temperature on impact wear morphology and properties of 30Cr3Mo2WNi hot working die steel were investigated by means of SEM, TEM, hardness and impact wear tests. In the tempering temperatures from 300℃ to 680℃, the hardness of the steel decreases and the impact toughness increases with increasing tempering temperature, while a secondary hardening with maximum hardness value of 48.6 HRC was achieved at 550℃. Fatigue delamination wear is the main mechanism during the impact wear of the experimental steel, and three damage features can be identified with different tempering temperatures. Brittle fatigue cracks are easy to occur at low tempered temperature of 300℃. Ductile fatigue cracks occurs at medium temperatures. Surfaces of steel tempered are extruded at high temperature of 680℃.